Eruptions in focus: cefadroxil and the uncommon realm of fixed-drug reactions: a case report - Agrawal, Palak; Kunkulol, Rahul; Ghodke, Kartik Dhananjay (International Journal of Basic & Clinical Pharmacology, 2024)
This case report explores a rare case of localized fixed-drug eruption (FDE) induced by cefadroxil, a first-generation cephalosporin. FDE, characterized by recurrent lichenoid lesions at specific sites upon drug exposure, is an immunological cutaneous adverse reaction. The incidence of FDE due to cephalosporins is infrequently reported, making this case noteworthy. We present a 51-year-old male who developed brownish-black patches and painful blisters on his extremities after initiating treatment with Cefadroxil for a minor toe injury. The patient’s symptoms, clinical course, and subsequent recovery are detailed. Treatment involved corticosteroids, antibiotics, and topical agents. The report also provides immunological insights into FDE pathogenesis, involving CD8+ memory T cells, cytokine production, and the role of CD4+ regulatory T cells. While the exact pathogenesis of FDE remains elusive, this report sheds light on the mechanisms contributing to the self-limited nature of these eruptions. Causality assessment using the Naranjo algorithm categorized the association between cefadroxil and FDE as probable. This case report contributes to the limited literature on FDE caused by cephalosporins and underscores the importance of recognizing and managing such dermatological reactions. The broader implications of understanding FDE pathogenesis and the rarity of cephalosporin-induced cases provides valuable insights for clinicians and researchers.